Preferences for redistribution and perception of fairness: An experimental study - Ruben Durante; Louis Putterman (Brown University, Department of Economics, 2007)
Why is there significant political support for progressive taxation and equalizing government transfers in western democracies? Possibilities include individual socail preferences for a less unequal distribution than what market forces alone would dictate, demand for social insurance, or successful political coalitions to redistribute away from the rich. We study the relative importance of fairness preferences, risk aversion, and self-interest in determining support for redistribution through a set of experiments in which a large number of subjects are asked to choose what level of taxation to implement under different decision conditions and with four alternative determinants of pre-tax income (two task-based, one random, and one based on socio-economic background). Treatments using varying costs of redistribution to the decision-maker and efficiency losses to recipients are used to study willingness to pay for redistribution and concern for aggregate inefficiency. Most of our subjects prefer that there be less inequality among others and demand for redistribution responds in predictable ways to the cost of taxation and to the dead-weigh loss associated with it. The external validity of the experiment is supported by the high correlation between tax decisions and political preferences. We also find evidence that preferred levels of redistribution are highly responsive to whether pre-tax incomes are determined according to task performance, a trend that is much more evident among men than among woman. Comparisons between redistributive choices under different experimental conditinos provide interesting insights with regard to the relative importance of inequality aversion and self-interest when choosing under uncertainty and when uncertainty is resolved. In the first case, individuals expectation about their future position in the income distribution has a considerable impact on their tax choices. When sure of the effect on their own earnings, subjects tax choices are primarily goverened by self-interest, but fairness preferences continue to play a role.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; Soziale Wohlfahrtsfunktion; Soziale Gerechtigkeit; Test